2019
DOI: 10.1515/ijb-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Extrapolation Method for Cox Regression Model with a Mixture of Berkson and Classical Errors in the Covariates using Calibration Data

Abstract: Many biomedical or epidemiological studies often aim to assess the association between the time to an event of interest and some covariates under the Cox proportional hazards model. However, a problem is that the covariate data routinely involve measurement error, which may be of classical type, Berkson type or a combination of both types. The issue of Cox regression with error-prone covariates has been well-discussed in the statistical literature, which has focused mainly on classical error so far. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Mallick et al (2002) found that the mixture error bias in their relative risks for thyroid disease and radiation fallout ranged from 3.2 to 42.7% [15]. Tapsoba et al (2019) studying medications in HIV patients report biases from 0 to 22% depending on the correction method [33]. These values are close to our findings, as is their assumed percentage of Berkson error in the exposure that lies between 20 and 80%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Mallick et al (2002) found that the mixture error bias in their relative risks for thyroid disease and radiation fallout ranged from 3.2 to 42.7% [15]. Tapsoba et al (2019) studying medications in HIV patients report biases from 0 to 22% depending on the correction method [33]. These values are close to our findings, as is their assumed percentage of Berkson error in the exposure that lies between 20 and 80%.…”
Section: Discussionsupporting
confidence: 84%
“…The mixture model consists of the variables described in eqs. 1 and 2, along with a latent intermediate variable L, between A and C, that allows for mixtures of Berkson and classical error as described elsewhere [15,33]. Briefly, the model is:…”
Section: Mixture Errormentioning
confidence: 99%
“…Apanasovich et al (2009) developed the basic theory for SIMEX in semiparametric problems using kernel‐based estimation methods. Tapsoba et al (2019) applied SIMEX to Cox regression analysis when some covariates are possibly contaminated with a mixture of Berkson and classical errors.…”
Section: Biomarker Measurement Error In Regression Analysismentioning
confidence: 99%
“…The outcome variable Y was assigned by sampling from normal distribution under a model of the form Y = 1 + 2Z + 1T + N(0, 1). Simulations were conducted for scenarios where ω T|Z = 0, 1, 2, and for scenarios where σ 2 X|T = 0.2, 0.5, 1, similar to the ranges of measurement errors that have been posited in simulations in a range of epidemiologic substantive areas (16)(17)(18).…”
Section: Simulation Examplementioning
confidence: 99%